RINCONES DE LECTURA PARA ESTIMULAR EL DESARROLLO DEL LENGUAJE, EN LOS NIÑOS DE EDUCACIÓN INICIAL II - PERALTA VERA CINDY DAMARIS (2024)
This research examines how the implementation of reading corners impacts the language development of children in Early Childhood Education II at Emigdio Esparza Educational Unit in Babahoyo, Los Ríos Province. The study identifies a lack of pedagogical strategies and adapted resources to stimulate each student's linguistic development. This oversight in addressing diversity may create barriers to learning and participation, affecting comprehensive development and the sense of belonging among children. The overarching objective of the research is to establish reading corners aimed at promoting language development in Early Childhood Education II. Specific objectives include analyzing the importance of early stimulation in linguistic development, identifying the most effective materials and activities for reading corners, and determining the impact of these corners on children's language development. The methodology employed comprised participant observation, semi-structured interviews, and institutional document analysis. Findings underscore the significance of reading corners in children's language development. As a potential conclusion, implementing a reading corner for Early Childhood Education II positively influences children's comprehensive development, fostering linguistic skills, creativity, and reading comprehension from an early age. A recommended approach includes strengthening a school culture that promotes a love for reading from early childhood